Content Resources for Psychological Support of Families with Problem Children - Mushkevych , Myroslava (Psychological Counseling and Psychotherapy, 2021)
The article presents a model of psychological support for families with problem children, describes a system of events that has a clearly structured and organized nature and is built on psychological principles. The latter is provided with the help of special forms and methods of the program of psychological support, which include: 1) at the level of the psychodiagnostic stage, standardized and projective techniques; 2) at the level of the psychoeducational stage - psycho-preventive techniques and educational activities in accordance with empirical data regarding gaps in psychological knowledge and the needs of the subjects themselves; 3) at the level of the psycho-counseling stage - conversation and interpretation as specific forms of providing psychological assistance focused on personality and interaction among family members, their assimilation of effective ways to independently solve problems; 4) at the level of the psychotherapeutic stage - interpretation and discussion of the results obtained in the process of empirical research, conducting psychotechniques "Family Chest", "Writing a Fairy Tale", "Family Diagram" with subsequent feedback.